Morphology and molecular phylogeny of Macrobrachium saengphani sp. nov. (Decapoda: Palaemonidae) from Northern Thailand - Saengphan, Nukul; Panijpan, Bhinyo; Senapin, Saengchan; Suksomnit, Auaree; Phiwsaiya, Kornsunee (Zootaxa, 2020)
A small wild prawn of the genus Macrobrachium, found in Chiang Rai Province, Northern Thailand has some morphological features resembling four other closely related species, M. lanchesteri, M. peguense, M. kunjuramani, and M. chainatense. However, it is distinguishable from the above species in terms of distinctive golden colored antennules; number of teeth on the rostrum; number of teeth on the cutting edges of the second pereiopod; and length of carpus relative to that of chela on the second pereiopod. Moreover, DNA analysis places it far apart on the phylogenetic tree from the related species in the genus.